DISC - the dust impact sensor and counter on-board Comet Interceptor: Characterization of the dust coma of a dynamically new comet. Issue 8 (15th April 2023) - Della Corte, V.; Ferretti, S.; Piccirillo, A.M.; Zakharov, V.; Di Paolo, F.; Rotundi, A.; Ammannito, E.; Amoroso, M.; Bertini, I.; Di Donato, P.; Ferraioli, G.; Fiscale, S.; et al.
Abstract: The Comet Interceptor space mission, selected by ESA in June 2019 as the first F-Class mission, will study a dynamically new comet or an interstellar object by a unique multi-point 'snapshot' measurement. The mission design will allow to complement previous single spacecraft's fly-by cometary observations. The Dust Impact Sensor and Counter (DISC), devoted to the dust coma characterization, is part of the payload selected for Comet Interceptor. It will be mounted on-board two of the three spacecraft, as part of the Dust-Fields-Plasma (DFP) suite, dedicated to understand further: 1) dust in the coma; 2) magnetic field; 3) plasma and energetic neutral atoms. DISC architecture originates from the Impact Sensor subsystems, part of the Grain Impact Analyzer and Dust Accumulator (GIADA) that successfully flew on-board the ESA/Rosetta spacecraft. DISC main scientific objectives are: 1) to define the dust mass distribution for particles in the mass range 10 −15 − 10 −8 kg ejected from the cometary nucleus; 2) to count dust particles with mass > 10 −15 kg; 3) to constrain dust particle density/structure. In this paper, we describe DISC design, aims, methods, feasibility and performances evaluations, carried out by real and simulated dust impacts and by retrieving the number of particles, and their corresponding momentum, using the Comet Interceptor's Engineering Dust Coma Model.